Selection of optimal parameters for obtaining whipped products from egg whites - Magomedov G.; Lobosova L.; Rozhkov S.; Selina N. (Техника и технология пищевых производств)
Development of new types of functional whipped confectionery of souffle type in which animal proteins are replaced with vegetable ones is promising and of high priority. The author proposed to introduce top grade wheat flour into the recipe of the whipped product and lemon zest as an enriching additive. Experimental studies were carried out under laboratory conditions of the department of technology of bakery, confectionery, macaroni and grain processing industries of Voronezh State University of Engineering Technologies. The whipped product was obtained using an experimental whipping device developed by the staff of the department. The author justified the choice of the components in the recipe. The optimum modes of obtaining the whipped product which includes top grade wheat flour, water, citric acid, agar, white sugar, molasses, and lemon zest were selected using the experimental-statistical approach. The main cooking parameters are the duration of whipping (seconds); rotation frequency of the whipping parts (minutes-1), an output parameter (the volume weight of the final product, g/cm3). The results are the following: duration of the mass whipping x1 = 379 s-1, rotation speed of the whipping parts x2 = 651 min-1. The author determined quality indicators of the final whipped product. It has a good form-retaining ability, uniform and fine-porous structure, slightly creamy color, and slight taste of lemon zest. Mass fraction of dry matter is 76%, density – 0.43 g/cm3. The obtained product has original organoleptic parameters and higher nutritional value. The author did not include any food color additives and flavoring agents. For that reason the product can be recommended not only to people suffering from egg white intolerance, but also to all categories of consumers.